Banks’ loan loss provisioning behaviour and procyclicality across Central and Eastern European countries joined the European Union in 2004 - Makaricevs, Aleksandrs (2011)
This paper investigates how provisioning behaviour across Central and Eastern European commercial banks is related to the business cycle, income smoothing and capital management. The analysis is conducted on a sample of 52 banks from five European Union countries over the period from 2004 to 2010. These countries are: Latvia, Lithuania, Estonia, Slovenia and Slovakia.